Implementasi Tahapan APOS pada Analisis Kemampuan Pemahaman Konsep Mahasiswa dalam Menyelesaikan Soal Matriks - Filda Febrinita; Wahyu Dwi Puspitasari; Wahid Ibnu Zaman (Jurnal Tadris Matematika, 2022)
Changes in the learning process during the pandemic affected student learning outcomes. As many as 68% of students score below 75 in computational mathematics courses. These results are not comparable to learning outcomes when learning takes place offline. The results of the interviews show that students have difficulty understanding the material when learning is done online. For this reason, a qualitative descriptive study was carried out which aimed to analyze and describe students' conceptual understanding abilities in solving matrix problems using the APOS stages. The research subjects were 3 students of the informatics engineering study program who had taken computational mathematics courses and received matrix material, were in the category of students with low, medium, and high conceptual understanding, and were able to communicate their thoughts orally and in writing. Data collection techniques were carried out through written tests, interviews, and observations. The results showed that students with low conceptual understanding were able to solve matrix problems up to the object stage and made calculation mistakes. Students with a moderate understanding of concepts can solve matrix problems up to the schematic stage but are not careful in doing calculations. Meanwhile, students with high conceptual understanding can solve matrix questions up to the schematic stage, determine the correct answer, make conclusions, and reflect on the problem-solving obtained.